EFFECT OF BPJS (Social Insurance Administration Organization) RECEIVABLES MANAGEMENT AND INACTION OF BPJS CLAIM REPAYMENT ON PRIVATE HOSPITAL FINANCIAL FUNDS FLOW IN SURAKARTA - Dewi, Maya Widyana; Kusuma, Indra Lila; Saputra, Angga Febriawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
This study aims to examine the effect of BPJS (Social Insurance Administration Organization) receivable management, and the inaction of BPJS (Social Insurance Administration Organization) claim repayment, on private hospitals funds flow in Surakarta. The independent variable used is BPJS receivable management, the disbursement of payment of BPJS (Social Insurance Administration Organization) claims and the dependent variable is the flow of financial funds of private hospitals. The population in this study is a private hospital in collaboration with BPJS (Social Insurance Administration Organization) in Surakarta City. Samples were taken by purposive sampling method. The data analysis was performed using multiple linear regression, t test, F, and R2. Based on the results of the classical assimilation test analysis shows that this study is normally distributed and there is no multicollinearity, autocorrelation and heteroscedasticity in the regression model. The results of multiple linear coefficient equation Y = -3,551 + 1,019X1 + 4,018X2 + e. The results of the t test show that the BPJS (Social Insurance Administration Organization) receivable management variables and the inaction in repayment of BPJS claims partially have a significant effect on the flow of financial funds of private hospitals in Surakarta. And the F test results show that BPJS (Social Insurance Administration Organization) accounts receivable management variables and the repayment inaction of BPJS claims simultaneously affect the financial flow of private hospitals in Surakarta. Whereas, the R2 test results (determination coefficient) obtained R Square value of 0.990, which means that BPJS accounts receivable management variables and inactions in paying BPJS claims contribute 99% to the private Hospital financial flow funds, while the remaining 1% is influenced by other variables not examined in this research. Keywords : BPJS receivable management, repayment inaction of BPJS claims, and the financial funds flow of private hospitals.